Caverno-saphenous shunt for recurrent priapism - Jade Nguyen, MD; Sherwin Abdoli, MD; Christian Ochoa, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
We present a case of medication-induced priapism that was refractory to conventional urologic methods and required treatment with a caverno-saphenous bypass. The patient had been misusing an injectable erectile dysfunction medication consisting of alprostadil, papaverine, and phentolamine (Trimix), resulting in multiple episodes of priapism. His initial episodes of priapism were successfully treated with the traditional urologic algorithm, including phenylephrine, aspiration, and distal shunting. However, due to his continued medication misuse, these became ineffective, requiring proximal shunt surgery. Priapism requiring an extra-anatomic bypass is exceedingly rare. Following our proximal shunt surgery, he maintained partial sexual function, and his bypass remained patent.